Crystallizing Territorial Visions and Claims: Critical Mapping with Amazonian Kichwa Communities in Climate Change Politics - Kaulard, Anke; Paredes, Maritza; Gil, Danitza (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Over the past decade, Kichwa communities in San Martín, Peru, have faced growing tensions with environmental authorities over conservation and climate policies affecting forest access and use. Through a participatory action research project, we co-created a collaborative mapping methodology to document Indigenous visions on these transformations. This paper examines how critical mapping—integrating hand-drawn maps, storytelling, timelines, and digitalization—crystallizes Indigenous territoriality, enabling both internal reflection on territorial struggles and claims-making. Rather than being merely a response to imposed environmental governance, mapping becomes a practice that generates Indigenous agency and territorial autonomy. By enabling communities to represent their landscapes, history, and rights on their own terms, critical mapping becomes a powerful tool for grassroots political action.